Struktur Modal, Rasio Aktivitas, dan Ukuran Perusahaan terhadap Harga Saham Sektor Pertambangan yang Terdaftar di Jakarta Islamic Index - Fitria, Zahrotul; Sukardi, Agung Slamet (Penerbit Goodwood, 2024)
Purpose: This study aims to determine the influence of capital structure, activity ratio, and firm size on the stock prices of the mining sector listed on the Jakarta Islamic Index (JII). Methodology: The population of this study comprises mining sector companies listed on the Jakarta Islamic Index in 2019-2023. A purposive sampling technique was used. Results: The results of this study show that capital structure has no effect on stock prices, activity ratio has a positive and significant effect on stock prices, and company size has a negative and significant effect on stock prices. Limitations: This study used limited data for the 2019-2023 period, the results may not apply for different periods. The research sample is focused on mining sector companies; therefore, the results cannot be generalized to all companies or industries. This study does not consider macroeconomic or other factors. Contribution: This research is expected to provide a clear view of how mining sector companies can optimize stock prices in the capital market.